Factors influencing the course of post-COVID-19-related symptoms: A bidirectional cohort study among employees in health and welfare services in Germany - Steinke, Lara; Peters, Claudia; Nienhaus, Albert; Bethge, Matthias; Koch, Peter (GMS Hygiene and Infection Control)
Objective: The aim of this study was to determine the prevalence and trajectory of persistent symptoms following COVID-19 and to investigate factors influencing these among employees in the health and welfare services in Germany.Methods: This exploratory, mixed retro- and prospective cohort study using paper-and-pencil questionnaires was conducted among insured persons of the German Social Accident Insurance Institution for the health and welfare services with a SARS-CoV-2 infection in 2020. The baseline survey in February 2021 was succeeded by two follow-up surveys after 8 and 13 months. Demographic data, information on the acute illness and persistent symptoms were collected. Kaplan-Meier curves were created to visualize the course of recovery. Factors influencing the time to recovery were analyzed using multivariate Cox regressions.Results: Of the 4,325 people contacted, 2,053 took part in the survey (response rate: 47%). 1,810 people were included in the analysis. The most common persistent symptoms at all three survey time points were fatigue, concentration and memory problems, and dyspnea. After three months, 76.2% (95% CI: 74.2–78.2%) of participants still reported symptoms, after 18 months this dropped to 67.2% (95% CI: 65.0–69.4%). Significant risk factors for persistent symptoms were female sex (HR: 0.72; 95% CI: 0.58–0.88), age over 50 years (HR: 0.63; 95% CI: 0.50–0.78), a higher number of pre-existing illnesses and a higher number of severe acute symptoms. Respiratory and hormone-metabolic pre-existing conditions as well as severe dyspnea, smell or taste disorders, fatigue and memory or concentration problems during the acute COVID-19 illness also reduced the probability of complete recovery. Compared to other professions, working as a doctor had a protective effect (HR: 1.42; 95% CI: 1.11–1.80).Conclusion: More than a year after a COVID-19 illness, two-thirds of the healthcare staff surveyed reported persistent symptoms. This high number emphasizes the importance of long-term consequences of the COVID-19 pandemic for public health and the need for suitable therapy and rehabilitation concepts, especially for healthcare staff with post-COVID syndrome.